The vertex is at (-3, 4)
This can be found by looking at the basic form of vertex form:
y = (x - h)^2 + k
In this basic form the vertex is (h, k). By looking at what is plugged into the equation, it is clear that h = -3 and k = 4. This means the vertex is at (-3, 4).
The y-intercept is at 13. To find this we must first square the parenthesis and get the equation into standard form.
y = (x + 3)^2 + 4
y = x^2 + 6x + 9 + 4
y = x^2 + 6x + 13
Now we know that the y-intercept is equal to the constant, which is the last number in the equation.